Distribusi Southeast Asia Ovalocytosis (SAO) pada Berbagai Populasi Masyarakat di Kepulauan Sunda Kecil - Lanni, Fransiska (Biota : Jurnal Ilmiah Ilmu-Ilmu Hayati, 2004)
The presence of some genetic markers related to malaria as hemoglobinopathies, enzymophaties and ovalocytosis in populations of Lesser Sunda Islands  are presumed to be quite high, since this archipelago is mostly malaria endemic. To elucidate the problem, a series of observations had been done among  579 blood samples which were collected from five different populations (Balinese, Sasak, Sumbawanese, Sumbanese,  and Alorese) representing inhibitant of Lesser Sunda Islands. In this paper we present the distribution of Southeast Asia Ovalocytosis (SAO) which was detected  by microscopic examination of the red blood cell morphology. Among these, 38 subjects were suspected as SAO whereas the incidence ranges from 2.2% in Balinese to 15.7% in Alorese.  It was predicted that the high incidence of SAO in Alorese might be associated with malaria selection to compensate the absence of hemoglobinophaties in this population.